В. М. Даниленко та періодизація неоліту Південного Бугу: нові запитання до старих джерел - Гаскевич, Д.Л. (Археологія, 2013)
Поява радіовуглецевих дат і кількох альтернативних періодизацій буго-дністровського неоліту вимагають перевірки його відносної хронології, розробленої В.М. Даниленком. Тут визначаються методи та підходи, що дозволяють це зробити за неповноти джерел, здобутих у 1950-х рр. Периодизация неолита Побужья является основой относительной хронологии всего неолита территории Украины. Созданная В.Н. Даниленко в конце 1950-х гг., она неоднократно критиковалась и пересматривалась. Появление ее новых вариантов, а также неоднозначных серий 14С дат вынуждают по-новому взглянуть на первоисточники, лежащие в основе периодизации буго-днестровского неолита. Критический анализ полевой документации и публикаций В.Н. Даниленко свидетельствует о неполноте приведенной в них информации, предубежденности в ее изложении и интерпретации. Причиной этого были сложные условия проведения спасательных раскопок, а также личные качества и специфика научного мировоззрения ученого.
Следовательно, при проверке периодизации культуры следует учитывать недостатки имеющихся источников и опираться на результаты новых полевых работ. Но затопление водохранилищами большинства раскопанных В.Н. Даниленко памятников делает невозможной полевую проверку его стратиграфических наблюдений. Это, а также медленный темп накопления новых фактологических данных, переносит акцент исследования на рассмотрение старых источников. Наиболее информативными из них являются находки посуды. Применение формализированных методов описания сосудов с последующим анализом сочетаемости их признаков позволят проверить периодизацию В.Н. Даниленко даже невзирая на недостатки полевой документации, отсутствие стратифицированных контекстов и закрытых комплексов, утрату части находок. Division into periods of the Neolithic in the Buh River region is the base of the relative chronology of the whole Neolithic at Ukrainian territory. Developed by V.M. Danylenko at the end of the 1950-s, it was repeatedly criticized and reviewed. The advent its new versions, as well as ambiguous series of 14C dates makes the author to consider in a new way the sources laying in the base of division into the periods of the Neolithic at the Buh and Dnister Rivers area. Critical analysis of field documentation and publications by V.M. Danylenko evidence that the information presented there is not complete, partial in its statement and interpretation. The reason for that were the complicated conditions the rescue excavations, as well as the scholar’s personal qualities and peculiarity of scientific outlook.
Consequently, during the review of division the culture into the periods one should take into consideration the drawbacks of the sources available and lean on the results of the new field works. Flooding by the reservoirs of most of the sites excavated by V.M. Danylenko makes the field check of his stratigraphic observations impossible. This fact and also slow pass of the new factual data accumulation transfers the accent of the research to the old sources consideration. Finds of vessels are the most informative of them. Usage of formalizing methods in vessels description with consequent analysis of their features combination allows the author to check V.M. Danylenko’s division into periods despite the drawbacks of field documentation, lack of stratigraphic contexts and closed complexes, and loss of part of the finds.